Motivations for industry stakeholders in China, Vietnam, Thailand and Malaysia to improve livestock welfare - Sinclair, Michelle; Idrus, Zulkifli; van Nhiem, Duong; Katawatin, Suporn; Todd, Brendon; Burns, Georgette Leah; Phillips, Clive J. C. (MDPI, 2019)
Understanding what might motivate livestock stakeholders to improve animal welfare is useful information when developing initiatives that benefit from stakeholder engagement. This study was designed to assess the strength of motivating drivers in the development of attitudes to animal welfare, and the factors that impacted their ability to improve animal welfare. During a series of qualitative focus group sessions with livestock leaders across the same countries (Malaysia, China, Vietnam and Thailand), the current study presented livestock leaders (n = 139) with the most significant results in their country, and collected data pertaining to the meaning and applicability of these results. This data was then subject to thematic analysis to identify salient and repeated motivating factors and meanings. This process revealed a complex picture of relationships between motivators and the contexts that drive them. Figures are presented to begin illustrating these relationships. Some strong motivators were uncovered that were previously rated low in the survey (i.e., financial benefit) or not included at all (e.g., food safety). This paper also presents the opportunity to better understand the strength and relationship of extrinsic and intrinsic motivational forces behind animal welfare improvement.